2014
DOI: 10.1037/hea0000133
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and responses to couple conflict: Implications for cardiovascular risk.

Abstract: This was the first investigation to document emotional and cardiovascular responses to couple conflict in veterans with PTSD and their partners. PTSD was associated with greater frequency and severity of couple conflict, and greater anger and cardiovascular reactivity to conflict discussions. Anger and physiological responses to couple discord might contribute to CHD risk in veterans with PTSD, and perhaps their partners, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
6
29
0
Order By: Relevance
“…Service members with PTSD scored in the clinical range (Antony et al, 1998) on both depression ( M = 18.39, SD = 10.59) and anxiety ( M = 13.71, SD = 6.66) symptoms, although service members from the control group (depression M = .78, SD = 1.36; anxiety M = .81, SD = .86), partners of PTSD service members (depression M = 8.89, SD = 10.07; anxiety M = 5.09, SD = 7.05), and partners from the control group (depression M = 1.59, SD = 2.38; anxiety M = 1.50, SD = 2.08) all scored within the normal range. However, as previously reported by Caska et al (2014), in this sample both service members with PTSD and their partners endorsed higher levels of depression and anxiety symptoms than members of the control group.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…Service members with PTSD scored in the clinical range (Antony et al, 1998) on both depression ( M = 18.39, SD = 10.59) and anxiety ( M = 13.71, SD = 6.66) symptoms, although service members from the control group (depression M = .78, SD = 1.36; anxiety M = .81, SD = .86), partners of PTSD service members (depression M = 8.89, SD = 10.07; anxiety M = 5.09, SD = 7.05), and partners from the control group (depression M = 1.59, SD = 2.38; anxiety M = 1.50, SD = 2.08) all scored within the normal range. However, as previously reported by Caska et al (2014), in this sample both service members with PTSD and their partners endorsed higher levels of depression and anxiety symptoms than members of the control group.…”
Section: Methodssupporting
confidence: 80%
“…This study was conducted as part of a larger investigation of PTSD and the emotional and cardiovascular responses to conflict among military couples (see Caska et al, 2014). Couples were recruited from the Salt Lake City VA Medical Center (VAMC), post-deployment workshops, and state-sponsored programs for service members and their families.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one possible causal sequence could be that social stressors increase repressed anger, which increases blood pressure and tissue inflammation (Boylan & Ryff, 2013;Caska et al, 2014;Quartana & Burns, 2010;Quinn et al, 2014;Richter et al, 2011;Sanchez-Gonzalez, May, Koutnik, & Fincham, in press;Shivpuri et al, 2011), which could produce bodily symptoms that increase health concerns in the individual. Alternatively, another causal sequence could be that pre-existing health concerns increase perceived vulnerability to harassment or perceived need to conceal sexual orientation, which could increase repressed and angry ruminations about such social injustice.…”
Section: Study Limitations and Other Directions For Future Researchmentioning
confidence: 97%
“…Several studies have shown that military personnel suffering from trauma symptoms have less satisfied couple relationships (Erbes, 2011), and report more relationship problems Sayers, Farrow, Ross, & Oslin, 2009 Trauma symptoms are associated with self-reports of more negative couple communication, specifically greater conflict and less warmth (Caska et al, 2014). Miller and colleagues (2013) were the first to look at the impact of PTSD symptoms on observed couple communication.…”
Section: Trauma and Military Couple Relationshipsmentioning
confidence: 99%